Emulsion polymerization routes to chemically anisotropic particles - Mock, Eric B (Langmuir : the ACS journal of surfaces and colloids, 2010)
Methods are presented to synthesize suspensions of chemically and shape anisotropic colloids on submicrometer length scales. Particles are synthesized through seeded emulsion polymerization where a weakly cross-linked seed is swollen with monomer that phase separates at the reaction temperature resulting in a protrusion. The final particles can be considered to be composed of interpenetrating spheres. pH-sensitive anisotropy is created through the use of different surface coatings on each of the interpenetrating spheres. Dark-field imaging, dynamic light scattering, and scanning electron microscopy are used to characterize the particles